Cséplő Gyuri - Schiffer, Pál (Hunnia Filmstúdió ; Balázs Béla Stúdió, 1978)
Duration: 01:43:00 This situational documentary tells the saga of an intelligent, ambitious young Gypsy man who, without almost any schooling, goes from his isolated village to the capital, Budapest to find work. He studies and works but finds himself constantly discriminated against due to his ethnicity. Finally, he decides to return home but realizes that the time away has changed him considerably and his old life has become a stranger to him.